2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580030
|View full text |Cite
|
Sign up to set email alerts
|

Observability-based optimization for flow sensing and control of an underwater vehicle in a uniform flowfield

Abstract: Abstract-This paper describes how an underwater vehicle can control its motion by sensing the surrounding flowfield and using the sensor measurements in a dynamic feedback controller. Limitations in existing sensing modalities for flowfield estimation are mitigated by using a fish-inspired distributed sensor array and a nonlinear observer. Estimation performance is further increased by optimizing sensor placement on the vehicle body. We optimize sensor placement along a streamlined body using measures of flowf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…In their work, Ham and Brown demonstrated that the eigenvalues and eigenvectors of the error covariance matrix, when properly normalized, provide more insight into the estimability of linear combination of states, thereby supplying the previously commented deficiency of the covariance analysis. Ham and Brown’s estimability approach had been successfully employed for the evaluation of the multiposition alignment [53], in-flight alignment [46,54], aided alignment [55,56], alignment on a rocking base [57], INS/GNSS integration [48,58], as well as in several other applications not related to inertial navigation [59,60,61]. …”
Section: Introductionmentioning
confidence: 99%
“…In their work, Ham and Brown demonstrated that the eigenvalues and eigenvectors of the error covariance matrix, when properly normalized, provide more insight into the estimability of linear combination of states, thereby supplying the previously commented deficiency of the covariance analysis. Ham and Brown’s estimability approach had been successfully employed for the evaluation of the multiposition alignment [53], in-flight alignment [46,54], aided alignment [55,56], alignment on a rocking base [57], INS/GNSS integration [48,58], as well as in several other applications not related to inertial navigation [59,60,61]. …”
Section: Introductionmentioning
confidence: 99%
“…measurements (see, e.g., [12,30]). For a discrete set of measurements in time, the output of the linear time-varying system (5) can be written as …”
Section: B Observability Gramianmentioning
confidence: 99%
“…The observability of vortex flows was studied by Krener [11], where it was shown that Lagrangian measurements provide improved observability compared with Eulerian measurements. In [12], an observability-based sensor placement problem was solved by exhaustive search for sensor locations on a hydrofoil that improves angle-of-attack estimates, which were used in a feedback control of a Joukowski-foil model of an underwater vehicle. Wake estimation in aircraft formation flight was studied in [13], where pressure sensors on the leading edge of the trailing aircraft's wing were used in a vortex lattice simulation to track the lead aircraft's wake.…”
mentioning
confidence: 99%
“…From the viewpoint of the observer, the estimation problem can be likened to traditional target tracking [10]. This section provides the background on Bayes' theorem, Bayesian inference, and single target tracking with recursive Bayesian filtering.…”
Section: Recursive Bayesian Estimationmentioning
confidence: 99%